2015
DOI: 10.1002/ejoc.201500229
|View full text |Cite
|
Sign up to set email alerts
|

A Convergent Synthesis of 6‐O‐Branched β‐Glucan Oligosaccharides

Abstract: β-Glucans are important carbohydrate antigens on the surface of fungal cells useful for antifungal vaccine development. This paper has described a highly convergent and efficient strategy for the synthesis of structurally defined branched β-glucan oligosaccharides that can be used for detailed studies of β-glucans and for the design of β-glucan-based vaccines. The strategy was highlighted by assembling the title compounds via preactivation-based glycosylation with thioglycosides as glycosyl donors. It was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…The results obtained here and in a previous study 29 suggested that 1a – 3a elicited similar pattern and strength of immune responses as the KLH conjugate of an optimized linear oligo-β-glucan, i.e., octa-β-glucan. In the previous paper, we only reported the results with Titermax Gold as the adjuvant, but we also evaluated the linear oligo-β-glucan-KLH conjugates in the presence of CFA, which gave very similar results.…”
Section: Discussionsupporting
confidence: 84%
“…The results obtained here and in a previous study 29 suggested that 1a – 3a elicited similar pattern and strength of immune responses as the KLH conjugate of an optimized linear oligo-β-glucan, i.e., octa-β-glucan. In the previous paper, we only reported the results with Titermax Gold as the adjuvant, but we also evaluated the linear oligo-β-glucan-KLH conjugates in the presence of CFA, which gave very similar results.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to Globo-H 105 and arabinogalactan 116 , other complex oligosaccharides obtained by the preactivation-based thioglycoside method include branched oligosaccharides from glycolipid family including Lewis X pentasaccharide 117 , dimeric Lewis X 118 [ 63 ], tristearoyl lipomannan 119 [ 64 ], gangliosides GM1 120 [ 65 ] and GM2 121 ( Fig. 5 ) [ 66 ], microbial glycans such as the heptasaccharide repeating unit of type V group B Streptococcus capsular polysaccharide 122 [ 67 ], β-glucan oligosaccharides 123 from fungal cells [ 68 69 ], oligomannan containing multiple challenging β-mannosyl linkages 124 [ 54 ] ( Fig. 6 ), chitotetraose [ 70 ], mammalian glycans including complex type bisected N-glycan dodecasaccharide 125 [ 71 ], glycosaminoglycans including hyaluronic acid oligosaccharides 126 [ 72 73 ] ( Fig.…”
Section: Reviewmentioning
confidence: 99%
“…Huang and Ye groups [ 10 ] firstly established the concept of preactivation‐based one‐pot glycosylation, which has been used for a large quantity of oligosaccharides and polysaccharides synthesis. [ 47‐58 ]…”
Section: Application Of Preactivation Strategy In the Assembly Of Olimentioning
confidence: 99%